Ethics in groups - Tenbrunsel, Ann E.; Wageman, Ruth (Emerald, 2006)
The eighth volume on Managing Groups in Teams focuses on the forces that perpetuate or mitigate unethical behavior in groups. Group-based interactions, in comparison to individual interactions, pose unique challenges: the salient dimensions in the external environment can be different, within-group processes must be considered, and decision-making needs to be analyzed within a group-based context. The authors in this volume reflect on these forces and their role in unethical behavior. In the external environment, legal and ethical standards, sanctioning systems, the strategic fracturing of knowledge within organizations, and the communication medium used in virtual teams are identified as important influences on unethical behavior in group settings. Within the group, it is argued that certain processes such as social cohesion, group-level envy, and the intersection of self-interest and social identity are influential in ethical dilemmas. And, at the decision-making level, an examination of ethical decision-making within groups suggests that perspective taking by individual members, the felt pressure to avoid in-group favoritism by minorities, and intergenerational decisions must be taken into account. Together, these articles underscore the importance of considering the role that groups play in unethical behavior and are an essential source of information for those who wish to understand how unethical decisions are perpetuated within groups and organizations.
Keywords: Business & Economics -- Human Resources & Personnel Management.; Social Science -- General.; Organizational theory & behaviour.; Personnel & human resources management.; Ethics.; Group decision making.; elektronické knihy; electronic books